2019
DOI: 10.1177/0883073819837465
|View full text |Cite
|
Sign up to set email alerts
|

Perampanel Pharmacokinetics in Children: Correlation of Dose With Serum Concentrations

Abstract: Enzyme-inducing antiseizure drugs taken concomitantly with perampanel are known to influence perampanel serum concentrations. In this study, we examined perampanel dosage, serum concentrations, and the effect of concomitant enzyme-inducing antiseizure drugs in children for a 3-year period. A retrospective chart review determined patient age, weight, perampanel serum concentration and prescribed dose, and concomitant drugs. Of 87 patients included in the study, 41 were prescribed an enzyme-inducing antiseizure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Concomitant use of carbamazepine and oxcarbazepine was negatively correlated to PER C/D in our study. This is in accordance with previous reports that the concomitant use of enzyme-inducing AEDs could result in lower PER concentrations or C/D, both in children and adults ( Patsalos et al, 2016 ; Gaudio et al, 2019 ; Ikemoto et al, 2019 ; Ishikawa et al, 2019 ). Carbamazepine could increase the clearance of PER in a population pharmacokinetic analysis ( Fujita et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…Concomitant use of carbamazepine and oxcarbazepine was negatively correlated to PER C/D in our study. This is in accordance with previous reports that the concomitant use of enzyme-inducing AEDs could result in lower PER concentrations or C/D, both in children and adults ( Patsalos et al, 2016 ; Gaudio et al, 2019 ; Ikemoto et al, 2019 ; Ishikawa et al, 2019 ). Carbamazepine could increase the clearance of PER in a population pharmacokinetic analysis ( Fujita et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…5B, no significant correlation (r 5 0.430) was found between PER concentrations and weight-adjusted dose. However, the correlation could be significantly improved if we separate patients into concomitant enzyme-inducing ASMs groups (r 5 0.628) and concomitant non-enzyme-inducing ASMs groups (r 5 0.624), which was consistent with previous studies in children and adults [5,6,8]. What's more, the concomitant use of enzyme-inducing ASMs resulted in a marked decrease of the regression equation slope (2254.2 versus 1037.8), which was also in line with previous studies [6,26].…”
Section: Plasma Concentrationssupporting
confidence: 88%
“…Several studies have confirmed the significant association between dose-exposure (plasma concentration)-effectadverse events (AEs) of PER in adult and pediatric patients with epilepsy [5][6][7][8][9], but the reference concentration ranges of PER are still controversial [5,10]. On the other hand, PER is substantially (approximately 95%) bound to plasma proteins [11] and metabolized by cytochrome P450 (CYP450) enzyme, especially for CYP3A4 [9,[12][13][14], which partly determine the efficacy and AEs related to the plasma concentration of PER [5].…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies showed that concomitant use of PHT or CBZ leads to a reduction in the serum concentration of perampanel by 50%-70% [2,3]. Recently, perampanel was approved for clinical use in patients aged under 12 years, and its concentration was found to be significantly impacted by inducers in this population [4][5][6]. Therapeutic drug monitoring (TDM) for perampanel can be helpful for predicting the extent of drug interactions and adjusting the dose of perampanel in patients of all ages.…”
Section: Introductionmentioning
confidence: 99%